Effect of Lanthanum Oxide on the Activity Ni-Co/Diatomite Catalysts in Dry Reforming of Methane - G.Y. Yergaziyeva; E. Kutelia; K. Dossumov; D. Gventsadze; N. Jalabadze; T. Dzigrashvili; L. Nadaraia; O. Tsurtsumia; M.M. Anissova; M.M. Mambetova; B. Eristavi; N. Khudaibergenov (Eurasian Chemico-Technological Journal, 2023)
The effect of modifying additive (La2О3) on the activity of Ni-Co oxides was studied for the dry reforming of methane (DRM). The catalysts were prepared by impregnation of the granulated diatomite (D) and characterized by SEM, EDX, H2-TPR, XRD, and AES. It is shown that the addition of 1.5 wt.% La2O3 into the Ni-Co/D composition leads to an increase in the activity of the catalyst, providing a methane conversion that is close under thermodynamic equilibrium conditions in the temperature range of 700‒850 °С. The highest activity is achieved at T = 850 °C, the conversion of methane is 96%, and carbon dioxide is 92%. The addition of lanthanum oxide to the Ni-Co/D composition led to an increase in catalyst stability; after testing in the DRM reaction for 360 min, the deactivation coefficient for methane was 3.4%, and for carbon dioxide 2.5%. While significant deactivation is observed for Ni-Co/D, the deactivation coefficient for methane is 19%, and for carbon dioxide 36%. Many characterization results (SEM, H2-TPR, and XRD) confirm that Ni-Co-La/D has abundant surface oxygen and the presence of spinel structures that contribute to the reactivity of CH4 and CO2, which positively affect its activity.